Implementation of platform for long‐term evolution cell perspective resource utilization analysis. Issue 2 (22nd December 2020) - Um, Jungsun; Kim, Igor; Park, Seungkeun
Abstract: As wireless communication continues to develop in limited frequency resource environments, it is becoming important to identify the state of spectrum utilization and predict the amount needed in future. It is essential to collect reliable information for data analysis. This paper introduces a platform that enables the gathering of the scheduling information of a long‐term evolution (LTE) cellular system without connecting to the network. A typical LTE terminal can confirm its assigned resource information using the configuration parameters delivered from a network. However, our platform receives and captures only the LTE signal over the air and then enables the estimation of the data relevant to scheduling for all terminals within an LTE cell. After extracting the control channel signal without loss from all LTE subframes, it detects valid downlink control information using the proposed algorithm, which is based on the error vector magnitude of depatterned symbols. We verify the reliability of the developed platform by comparing it with real data from mobile phones and service operators. The average difference in resource block utilization is only 0.28%.